1975
DOI: 10.1093/cvr/9.5.697
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of non-autonomic and autonomic components of iliac bed vascular resistance in renal hypertensive rabbits

Abstract: Iliac bed vascular resistance (IVR) was measured before and after pharmacological block of the autonomic effectors in unanaesthetized renal hypertensive and normotensive rabbits with previously implanted Doppler flowmeters. This permitted partitioning the resting IVR into a non-autonomic component (ie, steady-state IVR after block) and an autonomic component (ie, resting IVR minus non-autonomic IVR). When IVR was measured at the same mean arterial pressure (MAP) before and after block in each animal, the incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
1

Year Published

1977
1977
1985
1985

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 0 publications
6
35
1
Order By: Relevance
“…In the course of other studies in the rabbit we observed that the intravenous injection of guanethidine elicited a prolonged vasodilatation (White, 1967;West, Angus & Korner, 1975). Such a response has been reported previously in the rabbit (Kadzielawa, 1962).…”
Section: Introductionsupporting
confidence: 77%
See 4 more Smart Citations
“…In the course of other studies in the rabbit we observed that the intravenous injection of guanethidine elicited a prolonged vasodilatation (White, 1967;West, Angus & Korner, 1975). Such a response has been reported previously in the rabbit (Kadzielawa, 1962).…”
Section: Introductionsupporting
confidence: 77%
“…Administration of guanethidine resulted in pronounced reduction in blood pressure and HVR ( Figure 1, left panels). When the guanethidine injection was repeated 1 h later in these autonomically blocked animals, the haemodynamic effects were similar to those observed after the first injection ( Figure 1, middle) despite good evidence of effective neural block at this time (West et al, 1975). When the sympathetic vasoconstriction was initially blocked with phenoxybenzamine (6 mg/kg) instead of guanethidine (12.5 mg/kg), injection of guanethidine again resulted in a marked fall in HVR (Figure 1, right).…”
Section: Nature Of Vasodilator Response To Guanethidinesupporting
confidence: 60%
See 3 more Smart Citations